Power analysis: an introduction for the life sciences - Colegrave, Nick; Ruxton, Graeme D. (Oxford biology primers, 2021)
"Oxford Biology Primers: exploring the science of life There has never been a more exciting time to be a biologist. Not only do we understand more about the biological world than ever before, but we're using that understanding in ever-more creative and valuable ways. Our understanding of the way our genes work is being used to explore new ways to treat disease; our understanding of ecosystems is being used to explore more effective ways to protect the diversity of life on Earth; our understanding of plant science is being used to explore more sustainable ways to feed a growing human population. Use the Oxford Biology Primers to explore biology for yourself-to find out more about what scientists at the cutting edge of the subject are researching, and the biological problems they're trying to solve"--